A novel study to examine dependency of indoor temperature and PCM to reduce energy consumption in buildings. (1st July 2022) - Mustafa, Jawed; Almehmadi, Fahad Awjah; Alqaed, Saeed
Abstract: In our world, primary energy per capita in 2020 was 71.4 units while in many countries such as Kingdom of Saudi Arabia (KSA) this figure is very high (303.3 units). While more than 50% of electricity in Saudi Arabia is used in buildings, in this study, SP21-EK was utilized to fall the share of buildings in energy usage. In this numerical study, energy equations with momentum were developed. In addition, radiation was applied to the entire building through boundary conditions. Although in many studies, the outside temperature has been known as an influential parameter on the choice of PCM, in this study, the focus is on the internal temperature of the building and its effects. The indoor temperature depends on the air conditioning system settings and can be set as a single setpoint or interval one. For the first case, setpoints of 21–26 °C were defined and it was observed that at best setpoint (22 °C ) the presence of SP-21EK dropped energy demand by 43.2%, while for 26 °C, this value was 20%. The effect of PCM was investigated in scenarios of 21–23 °C, 21–24 °C, 21–25 °C and 21–26 °C . Energy saving owing to using SP21-EK was 20341, 18164, 15131 and 13160 kWh. It was found that the scenario of 21 − 23 °C that corresponds to the PCM phase transition (21–23 °C ) had the most positive results. Highlights: Using SP21-EK to fall the share of buildings in energy usage. At setpoints of 22 °C and 26 °C, the presence of SP-21EK dropped energy demand by 43.2% and 20%, respectively. Energy saving owing to using SP21-EK was 20341, 18164, 15131 and 13160 kWh.